The Influence of the Contextual Teaching Learning Model (CTL) on the Fourth-Grade Students’ Learning Outcomes on the Theme of Beautiful Togetherness - Simbolon, Rimma Iya; Sipayung, Regina; Silaban, Patri Janson; Lumbanraja, Bogor; Sari, Dyan Wulan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper discusses the influence of the contextual teaching and learning model on students’ learning outcomes on the beautiful theme of togetherness in Grade IV at SD Negeri 065013 Medan in the academic year 2023/2024. This study uses the quantitative method. The research population involved 30 grade IV students at SD 065013 Medan. The results imply that before the treatment students had an average learning outcome of 58.80 and the students did not meet the KKM. In addition, after being given the treatment, students had an average learning outcome of 82.63. With a normality testing result of 0.200, the conclusion is that the data are normally distributed. The result of the correlation test is 0.761, which means rcount (0.761) > rtable (0.361), then Ha is accepted. Therefore, there is a significant influence between the use of the contextual teaching and learning model on the student’s learning outcomes in grade IV at SD Negeri 065013 Medan. It can be seen from the results of the t-test where the tcount 6.214 > ttable 2.042 so Ha is accepted. This shows that there is a significant positive influence from the use of the contextual teaching and learning model on students’ learning outcomes on the beautiful theme of togetherness in grade IV at SD Negeri 065013 Medan in the academic year 2023/2024